Energy efficient cluster-based routing scheme using type-2 fuzzy logic in underwater wireless sensor networks. (1st July 2022) - Bhaskarwar, Roshani V.; Pete, Dnyandeo J.
To enhance the energy and network lifetime in underwater wireless sensor networks, an optimum cluster-based routing protocol using fuzzy logic for UWSNs (OCR-FLU) is developed in the proposed work. Initially, the clusters are formed using K means algorithm. The existing literature in UWSNs has used type-1 fuzzy logic model (T1FL) in clustering approaches. In the proposed protocol, type-2 fuzzy logic (T2FL) system which is more accurate than the T1FL has been implemented to select an appropriate cluster head (CH) considering three parameters such as residual energy, distance to the surface sink, and packet delivery ratio. The CH then gathers data from each of its cluster members in a TDMA fashion and sends it to the sink via forwarder nodes based on maximum fitness value. The simulation results show that the proposed OCR-FLU outperforms the existing algorithms MLCEE and FBR in terms of energy efficiency, throughput, PDR and network lifetime.